Seroprevalence and factors associated with hepatitis C coinfection among HIV-positive pregnant women at the University College Hospital, Ibadan, Nigeria (2016)
Aim: This study estimated the hepatitis C virus (HCV) prevalence in a population of human immunodeficiency virus (HIV) infected pregnant women, compared women who were positive or negative for HCV and described risk factors associated with HCV infection. Materials and Methods: A retrospective, case control study was conducted at the University College Hospital, Ibadan among 1821 women. Twenty‑six (1.65%) women were HCV positive, 139 (8.83%) were HBsAg positive and 1407 (89.33%) were negative for both viruses. Three patients (0.19%) were positive for both viruses. These patients, i.e., the HBsAg positive women and 246 women with no result, for either virus were excluded from analysis. Data from 1433 pregnant women is presented. Chi square test and student’s t‑test examined associations, with level of significance set at P < 0.05. Results: Overall, the mean age of the HCV positive women was lower (26.77 ± 6.53 vs. 28. 95 years ± 5.33; P = 0.04), most women had attained primary (28.49%) or secondary (42.44%) education, over 90% were married and heterosexual sex (88.67%) was the most likely risk for HIV. HCV prevalence was higher in the lower age groups (5% in the ≤ 19 years group, P = 0.021). The coinfected had more unmarried women (3.6% vs. 1.7%; P = 0.164) and more likely to indicate blood transfusion as a risk factor for HIV (6.2%; P = 0.34). Conclusion: Only age showed any signiﬁcant association with HCV infection. Lack of identifiable risk factors sum up challenges for developing screening strategies in sub‑Saharan Africa. Further studies will identify factors facilitating HCV transmission in the region.